Law (justice) and livestock economy of the Aymara of the South Andean: Prospects for communal development - Peña Jumpa, Antonio (2004)
The Aymaras of the Peruvian Andean South share an interesting knowledge about law and economics applied to their livestock activity. This essay wants to reflect on this point, although with two limitations: our knowledge in economics is not specialized and the sample of communities on which the study is based includes only two of the three ecological floors that make up the Southern Andes.